(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
According to Justice P.N. Bhagwati,[1] the child is a soul with being, a nature and capacities of its own, who must be helped to find them, to grow into their maturity, into fullness of physical and vital energy and the utmost breath, depth and height of its emotional, intellectual and spiritual being, otherwise there cannot be a healthy growth of nation. Now obviously children need special protection because of their tender age and physique, mental immaturity and incapacity to look after themselves. That is why there is growing realization in every part of the globe, that children must be brought up in an atmosphere of love and affection and under the tender care and attention of parents so that they may be able to attain full emotional, intellectual and spiritual stability and maturity and acquire self-confidence and self-respect and a balanced view of life with full appreciation and realization of the role which they have to play in the nation building process, without which the nation cannot develop and attain full prosperity, because a large segment of the society would then be left out of the development process. And for the protection of such valuable assets we need strong laws with universal applicability.